Research on active earth pressure of narrow cohesionless backfill against rigid walls considering the arching effect - Liu, Yanchen; Li, Renrong; Wang, Yu (Frontiers in Physics, 2025)
Retaining walls are usually located next to existing structures. This runs counter to the traditional theoretical presumption of semi-infinite space, making it unsuitable to continue applying Coulomb’s theory. In order to design retaining walls with narrow backfill, improving the established theory and seeking an economical design theory are necessary. This paper puts forward an analytical approach for estimating the active earth pressure of narrow backfills. The approach, based on the slice-element method, takes into account the arching effect. The results obtained are verified through centrifuge tests, numerical computations, and analytical methods. Additionally, parametric studies are conducted to gain a comprehensive understanding of problems related to earth pressure. These studies consider how sensitive design variables, such as the soil friction angle, the wall–soil interface friction angle, and the aspect ratio, influence the active thrust coefficient and the height of the application point of the active thrust from the base. To enable the practical utilization of this analytical approach, a simplified design table related to the standard Coulomb solutions is provided at the end.